Twin testosterone transfer hypothesis and the second‐to‐fourth digit ratio in females of same‐sex and opposite‐sex twin pairs: An exploratory study - Moses Banyeh; Martha Nyewie; Abdul‐Rafik Abdulai; Charles Nkansah; Gabriel Abbam; Thea Kangkpi; Kervin Edinam Zogli; Shafiat Omotoyosi Shittu; David Bure; Romarick Kofi Wemegah; Mikail Ihsan Azindow; Suleman Yakubu; et al. (Physiological Reports)
Abstract The twin testosterone transfer (TTT) hypothesis posits that females with male co‐twins (opposite‐sex, OS) might develop male‐typical traits due to higher prenatal testosterone exposure. This study explored whether females of OS have lower 2D:4D digit ratios and higher testosterone levels compared to females of same‐sex (SS) twin pairs. Conducted in Tamale from January to December 2022, the study included 40 participants aged 18–27 years: 10 males of OS, 10 females of OS, and 20 females of SS twin pairs. Digit ratios (2D:4D) and serum testosterone levels were measured using computer‐assisted analysis and ELISA, respectively. Results showed no significant differences in 2D:4D ratios between females of OS and SS twin pairs for either the right hand (0.960 ± 0.049 vs. 0.955 ± 0.042; p = 0.766) or the left hand (0.966 ± 0.048 vs. 0.968 ± 0.047; p = 0.908). Serum testosterone levels were lower in females of OS than females of SS twin pairs (0.4 ± 0.1 vs. 0.67 ± 0.34 nmol/L; p = 0.013), but this result was not significant after multiple testing corrections (p > 0.050). The findings indicate that the TTT hypothesis may not apply, or its effects on digit ratios and testosterone levels in females of OS twin pairs are weak and not statistically significant. Further studies involving larger samples are however, recommended.